Role of RNA in Molecular Diagnosis of MADD Patients - Célia Nogueira; Lisbeth Silva; Ana Marcão; Carmen Sousa; Helena Fonseca; Hugo Rocha; Teresa Campos; Elisa Leão Teles; Esmeralda Rodrigues; Patrícia Janeiro; Ana Gaspar; Laura Vilarinho (Biomedicines, 2021)
The electron-transfer flavoprotein dehydrogenase gene (ETFDH) encodes the ETF-ubiquinone oxidoreductase (ETF-QO) and has been reported to be the major cause of multiple acyl-CoA dehydrogenase deficiency (MADD). In this study, we present the clinical and molecular diagnostic challenges, at the DNA and RNA levels, involved in establishing the genotype of four MADD patients with novel ETFDH variants: a missense variant, two deep intronic variants and a gross deletion. RNA sequencing allowed the identification of the second causative allele in all studied patients. Simultaneous DNA and RNA investigation can increase the number of MADD patients that can be confirmed following the suggestive data results of an expanded newborn screening program. In clinical practice, accurate identification of pathogenic mutations is fundamental, particularly with regard to diagnostic, prognostic, therapeutic and ethical issues. Our study highlights the importance of RNA studies for a definitive molecular diagnosis of MADD patients, expands the background of ETFDH mutations and will be important in providing an accurate genetic counseling and a prenatal diagnosis for the affected families.